The Competency Model of Graduated student in Air cargo Management Program of Thailand: Civil Aviation Training Center Thailand - Jane Northaw; Pariyaporn Tungkunanan; Wattana Manon (My University, 2019)
Abstract This research aims to explore the competency model of students who graduated from the Air Cargo Management Program of Civil Aviation Training Center. The research methodology consists of studying the competency requirements of an aviation company and that of the students in the Air Cargo Management Program. The sampling group consists of administrators and staff of aviation companies, amounting to a total of 210 participants. The competency model of students who graduated from the Air Cargo Management Program was collected using the Quality Function Deployment (QFD) method. This produces a semantic model which was confirmed using the Focus group method. The areas focused are competencies in attribute, knowledge, and skills. The results show that the highest mean in the Attribute competency, where 4 topics consisting of 17 subtopics were researched, obtained a mean score of 4.15, and an important weight score of 2.79. The Second highest mean score was in the knowledge competency, where 7 topics consisting of 17 subtopics were researched, obtained a score of 3.72, and the highest important weight score of 2.59. And the third was the Skills competency; the mean 3.70, the highest important w eight score of 2.59 and there are 6 topics consisting of 17 subtopics.
Keywords: Quality and Supply Management